ANALYSIS OF INVENTORY SPARE PARTS SYSTEM AT UPT BALAI YASA PT. KAI - Irwan Sukendar; Brav Deva Bernardhi; Ares Pambudi (Jurnal Ilmiah Dinamika Teknik, 2019)
This study focuses on the Analysis of Inventory Systems at the Technical Implementation Unit (UPT) BALAI YASA PT. KAI Tegal. This UPT has the duty as the person in charge of maintenance of the PT KAI train and car information system in the Central Java area. In this UPT the inventory and maintenance records of spare parts are still manual and not yet integrated so that the history of the use of spare parts is not well-databaseed, Technical Service Requests for Maintenance of IT (Information Technology) units are still done verbally and have not been well documented so that daily reports are not real and not real neat. This UPT has not determined the optimal number of orders, the number of safety stock and reorder points as important variables in the inventory system. Application of information systems in the company's business activities is one way for business activities to run faster, more precisely, and efficiently. The design of an inventory system improvement is to determine the optimal order quantity, safety stock (SS), and reorder point (ROP). In addition, the inventory feature is also equipped with a menu of incoming goods, items out and standby calculations, which makes it easy for IT units to monitor the condition of existing safety stock.